Kar9 controls the nucleocytoplasmic distribution of yeast EB1 - Schweiggert, Jörg; Panigada, Davide; Na Tan, Ann; Liakopoulos, Dimitris (Cell cycle, 2016)
The precise temporal and spatial concentration of microtubule-associated proteins (MAPs) within the cell is fundamental to ensure chromosome segregation and correct spindle positioning. MAPs form an intricate web of interactions among each other and compete for binding sites on microtubules. Therefore, when assessing cellular phenotypes upon MAP up- or downregulation, it is important to consider the protein interaction network between individual MAPs. Here, we show that changes in the amounts of the spindle positioning factor Kar9 specifically affect the distribution of yeast EB1 on spindle microtubules, without influencing other microtubule-associated interacting partners of Kar9, i.e. yeast XMAP215 and CLIP-170. Alterations in the distribution of yeast EB1 explain chromosome segregation defects upon knockout, overexpression or stabilization of Kar9 and provide an example for non-linear effects on MAP behavior after perturbation of their equilibrium.